2022
DOI: 10.1002/pbc.29830
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐institutional analysis of central nervous system germ cell tumors in patients with Down syndrome

Abstract: Purpose: Primary germ cell tumors (GCTs) are the most common central nervous system (CNS) neoplasm in patients with Down syndrome (DS). However, a standard of care has not been established due to paucity of data. Methods:A retrospective multi-institutional analysis was conducted, in addition to a comprehensive review of the literature.Results: Ten patients from six institutions (five USA, one Brazil) were identified, in addition to 31 patients in the literature from 1975 to 2021. Of the 41 total patients (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Notably, the rarity of NGGCT, though linked with Down Syndrome in just one case in our series, warrants careful attention. A recent publication by Harris et al revealed an increased risk of treatment-related adverse events and long-term neurocognitive sequelae in this patient group, necessitating alternative therapeutic approaches (24). Some innovative cases have been reported, such as ASCT and brentuximab-vedotin for those with CD30-positive embryonal carcinoma (25).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the rarity of NGGCT, though linked with Down Syndrome in just one case in our series, warrants careful attention. A recent publication by Harris et al revealed an increased risk of treatment-related adverse events and long-term neurocognitive sequelae in this patient group, necessitating alternative therapeutic approaches (24). Some innovative cases have been reported, such as ASCT and brentuximab-vedotin for those with CD30-positive embryonal carcinoma (25).…”
Section: Discussionmentioning
confidence: 99%
“… 18 A specific example in children with DS is that germ cell tumours make up a disproportionate number of central nervous system tumours, with a higher percentage located in the basal ganglia, compared to the non-DS population. 19 …”
Section: Role Of T21 In Leukaemogenesismentioning
confidence: 99%